Analysis of the impact of covid-19 on mustahik and muzakki - Aminah; Ika Rarawahyuni (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2023)
The purposes of this study are to analyze the effect of the covid-19 pandemic on muzakki's loyalty, to analyze the impact of utilizing zakat funds on the average mustahik's income during the covid-19 pandemic, and to analyze changes in mustahik's income before and after assistance zakat funds with the CIBEST model. This type of research is field research using quantitative methods, where the data analysis technique uses the t-test and the CIBEST model. With a sample consisting of muzakki and mustahik, where the muzakki sample was 150 respondents and the mustahik sample was 119 respondents. The results of the analysis obtained from this study are The Covid-19 pandemic has affected the loyalty of muzakki, where this is caused by several things, including a decrease in the income of muzakki, there are muzakki who died during the pandemic and an increase in the number of mustahik due to the impact of covid-19 19, meaning that there are muzakki who become mustahik; Respondents felt very helpful with the zakat fund utilization program for mustahik during the Covid-19 pandemic. This is because during the pandemic there was a PSBB which greatly affected their income to meet their family's needs; The results of calculations using the CIBEST model show that all mustahik who are respondents in this study feel that there is a change in income for their families for the better after they receive productive zakat assistance funds.